2019
DOI: 10.1136/bmj.l5882
|View full text |Cite
|
Sign up to set email alerts
|

Which emollients are effective and acceptable for eczema in children?

Abstract: What you need to know • Although emollients alone can help reduce the symptoms of eczema and prevent flares, most people will need to use anti-inflammatory treatments such as topical corticosteroids of an appropriate strength and duration as well • Effectiveness and acceptability of emollients varies according to disease severity, body site, climate, container, and patient or carer preferences and beliefs • Based on current evidence, the "best" emollient is the one that the individual prefers after a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
(18 reference statements)
2
15
0
1
Order By: Relevance
“…Our study tested an intervention that was acceptable to parents and the use of emollients in the study is likely to closely reflect how emollients are recommended and used in the community. 28 Selection, detection, performance, and attrition biases are unlikely to explain the absence of a preventive effect. Eczema was measured using validated criteria, applied by trained researchers masked to the treatment intervention 1 year after use of the emollient had ceased.…”
Section: Discussionmentioning
confidence: 99%
“…Our study tested an intervention that was acceptable to parents and the use of emollients in the study is likely to closely reflect how emollients are recommended and used in the community. 28 Selection, detection, performance, and attrition biases are unlikely to explain the absence of a preventive effect. Eczema was measured using validated criteria, applied by trained researchers masked to the treatment intervention 1 year after use of the emollient had ceased.…”
Section: Discussionmentioning
confidence: 99%
“…Ridd et al . further highlighted the evidence gap on emollient use in AE by examining emollient efficacy and acceptability in paediatric AE 8 . This study supplemented a previous Cochrane review published in 2017 by an updated search and concluded that the evidence on whether some emollients were superior to others was inconclusive as most of the studies were of poor quality.…”
Section: Topical Therapiesmentioning
confidence: 72%
“…No consensus exists for the optimal time interval between the application of TCS and moisturisers, or which is to be applied first 17. The “best moisturiser” is the one that the patient prefers, works best for the patient, and is affordable 18…”
Section: How Are Moisturisers Being Applied?mentioning
confidence: 99%